Microplastics pollution in Indian marine environment: sources, effects and solutions - Josephine Anthony; Sureka Varalakshmi; Ashok Kumar Sekar; Kumar Thalavai Sivasankarasubbiah; Thilagam Harikrishnan; Vijaya Raghavan Rangamaran; Dharani Gopal; Kirubagaran Ramalingam (Frontiers in Marine Science)
Microplastic pollution has emerged as a significant environmental challenge globally, posing threats to biodiversity, marine life, and human health. Studies indicate that marine organisms, from plankton to larger fish species, and ultimately humans are ingesting microplastics, leading to physiological harm such as inflammation, digestive blockages, tissue injury, hormonal imbalance, reproductive failure and biomagnification through the food chain. Therefore, there arises an urgent need and demand for implementing effective and sustainable remediation solutions. Though, various mitigation technologies are developed, less information is available on the advantages and disadvantages of the technological advancements. The present review highlights the significant information available on the sources, types, transport of microplastics along with the analytical methods to detect the microplastic pollutions. The global perspective of microplastic pollutions with respect to Indian Marine scenario was highlighted. The recent and advanced mitigation technologies and solutions in preventing, reducing and recycling these microplastic pollutions were also addressed. This review further underscores the need for comprehensive strategies to monitor, manage and mitigate microplastic pollution, including policy interventions, public awareness campaigns, and sustainable waste management practices. Addressing this issue is essential for preserving the health of India’s marine ecosystems and safeguarding the livelihoods of mankind.